2015
DOI: 10.1007/s11144-015-0855-y
|View full text |Cite
|
Sign up to set email alerts
|

CO2 capture in humid gas using ZnO/activated carbon and ZnO reactivity with CO2

Abstract: Carbon dioxide capture with ZnO/activated carbon adsorbates and reactivity of ZnO particle with CO 2 are discussed for the effective CO 2 capture in humid exhaust gas. Coarse ZnO particles (d = 670 nm), and small diameters, d \ 20 nm, of zinc oxide particles on activated carbon supports were prepared. The amounts of CO 2 adsorbed on ZnO particles and activated carbon supports were measured and calculated. The calculated value and thermal gravimetric analysis results indicate that only the surface layer (\0.5 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“… Taira et al implemented ZnO for CO 2 adsorption from humid gases. According to their results, CO 2 chemisorption takes place on ZnO particles, and after an adsorption test, the carbonate species formed on the surface of ZnO particles still remained after being purged by N 2 gas . Kansha et al introduced a process for CO 2 chemical absorption by ZnO solids in a fluidized bed.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Taira et al implemented ZnO for CO 2 adsorption from humid gases. According to their results, CO 2 chemisorption takes place on ZnO particles, and after an adsorption test, the carbonate species formed on the surface of ZnO particles still remained after being purged by N 2 gas . Kansha et al introduced a process for CO 2 chemical absorption by ZnO solids in a fluidized bed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…According to their results, CO 2 chemisorption takes place on ZnO particles, and after an adsorption test, the carbonate species formed on the surface of ZnO particles still remained after being purged by N 2 gas. 53 Energy & Fuels surfaces by mixed O and Zn atoms and physisorb on singly terminated surfaces. 58 Many studies 26,27 have reported TiO 2 nanofluid as the best CO 2 nano-absorbent among CuO, MgO, SiO 2 , and Al 2 O 3 .…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…The above is confirmed for M(x) = Fe(II), Zn(II), La(III), Ce (III) and Sn(II) under 150 bar in [ 92 , 93 , 94 , 95 , 96 ]. Further, CaO [ 71 , 97 , 98 , 99 , 100 ], BeO [ 64 ], Co 3 O 4 [ 101 ], MgO [ 102 , 103 ], FeO, Fe 2 O 3 , Fe 3 O 4 [ 104 ], Li 2 O [ 66 , 105 ], CuO [ 106 , 107 ] and NiO [ 108 ] were used as sorbents in a CO 2 environment. ZnO has been also studied for CO 2 capturing in CO 2 environment using the pressure at 1–25 bar [ 109 , 110 , 111 , 112 ].…”
Section: Theoretical Calculations Of the Formation Of Metal Oxide Nan...mentioning
confidence: 99%